Fulfilling the Right of Education during Covid19 Pandemic Period: A Comparative Study - Hwian Christianto; Michelle Kristina (Jambura Law Review, 2022)
The right of education for citizens has been fulfilled diversely following the government policies. This study aimed to emphasize the importance of the education right and the imposition of criminal sanctions in order to protect the right of education during the Covid-19 Pandemic particularly in Indonesia, Japan and Australia. Normative juridical research methods described that government policies as outlined in the legislation constantly followed by criminal sanctions. The concept of education right was understood in a different way during the Covid-19 pandemic, as one of the derogable-right or adapted human right. For its fulfillment, some education right uses criminal sanctions as a primum remidium, an ultimum remidium, or does not impose criminal sanctions at all. The right of education still reman as a very important human right even during the pandemic period